Atalaia Catholica (1859)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Atalaia Catholica (1859)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Atalaia Catholica (1859)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Theatro do visconde de almeida-Garrrtt vol 4 philippa de vilhena - Almeida Garrett (Imprensa Nacional, 1859)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Literature

o judeo de verona ou as sociedades secretas na utalia obra historica - antonio bresciani (f. de paula pereira, 1859)
Keywords: 10.Cover Damage; 2.Damage; Condition: Poor; Hard Cover; History

Histore Generale des Auteurs Sacres et Ecclesiastques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1859)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Histore Generale des Auteurs Sacres et Ecclesiastques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1859)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Histore Generale des Auteurs Sacres et Ecclesiastques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1859)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Histore Generale des Auteurs Sacres et Ecclesiastques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1859)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Histoire Generale des Auterus Sacres - Ceillier, Remy (1859)
Keywords: 1.Conservation 保護; 2.Damage

Histoire Generale des Auterus Sacres - Ceillier, Remy (1859)
Keywords: 1.Conservation 保護; 2.Damage

Histoire Generale des Auterus Sacres - Ceillier, Remy (1859)
Keywords: 1.Conservation 保護; 2.Damage

Histoire Generale des Auterus Sacres - Ceillier, Remy (1859)
Keywords: 1.Conservation 保護; 2.Damage

M. T. Ciceronis Opera Omnia - Cicero, Marcus Tullius; Nobbe, Carolus Fridericus Augustus (Sumtibus Et Typis Caroli Tauchnitii., 1859)
Marcus Tullius Cicero (106–43 BCE) was a Roman philosopher, politician, lawyer, orator, political theorist, consul, and constitutionalist.
OCLC: 957502286
Keywords: 2.Damage; Condition: Fair; Hard Cover; Philosophy

diccionario da lingua portugueza para uso dos portuguezes e brazil[?]iros (editor-proprietario, 1859)
Keywords: 10.Cover Damage; 18.Bookworm; 8.Tear; Condition: Fair; Dictionaries; Hard Cover

Theatro do V. de Almeida Garrett - Garrett, Almeida (Imprensa Nacional, 1859)
OCLC: 1076591466
Keywords: 18.Bookworm; 22.stamp; Condition: Fair; Hard Cover

Theatro do Visconde de Almeida Garrett. V, A sobrinha do Marquez - Garrett, Almeida (Imprensa Nacional, 1859)
OCLC: 492492644
Keywords: 18.Bookworm; 2.Damage; Condition: Poor; Hard Cover; Théâtre (genre littéraire) portugais 19e siècle

Bullarum Diplomatum et Privilegiorum Sanctorum Romanorum Pontificum Taurinensis Editio - Gaude, Francisco (Seb. Franco, et Henrico Dalmazzo Editoribus, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Bullarum Diplomatum et Privilegiorum Sanctorum Romanorum Pontificum Taurinensis Editio - Gaude, Francisco (Seb. Franco, et Henrico Dalmazzo Editoribus, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Bullarum Diplomatum et Privilegiorum Sanctorum Romanorum Pontificum Taurinensis Editio - Gaude, Francisco (Seb. Franco, et Henrico Dalmazzo Editoribus, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Bullarum Diplomatum et Privilegiorum Sanctorum Romanorum Pontificum Taurinensis Editio - Gaude, Francisco (Seb. Franco, et Henrico Dalmazzo Editoribus, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Bullarum Diplomatum et Privilegiorum Sanctorum Romanorum Pontificum Taurinensis Editio - Gaude, Francisco (Seb. Franco, et Henrico Dalmazzo Editoribus, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Bullarum Diplomatum et Privilegiorum Sanctorum Romanorum Pontificum Taurinensis Editio - Gaude, Francisco (Seb. Franco, et Henrico Dalmazzo Editoribus, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Bullarum Diplomatum et Privilegiorum Sanctorum Romanorum Pontificum Taurinensis Editio - Gaude, Francisco (Seb. Franco, et Henrico Dalmazzo Editoribus, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Selecta e veteribus scriptoribus loca jussu regis fidelissimi in lucem edita et scholarum linguae Latinae usui adcommodata - Gomes de Moura, José Vicente (Typis Academicis, 1859)
OCLC: 15632336
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History; Literature

diccionario bibliographico portuguez - innocencio francisco de silva (Na Imprensa Nacional, 1859)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Dictionaries; Hard Cover

diccionario bibliographico portuguez - innocencio francisco de silva (Na Imprensa Nacional, 1859)
Keywords: 10.Cover Damage; 16.Waterstains; 18.Bookworm; 2.Damage; Condition: Poor; Dictionaries; Hard Cover

English cyclopaedia: a new dictionary of universal knowledge, conducted by C. Knight - Knight, Charles (bradbury and evans, 1859)
v1[?] title page missing
Keywords: 10.Cover Damage; 13.Page missing; 2.Damage; 8.Tear; Condition: Poor; Dictionaries; Hard Cover

Historia de Gil Braz de Santilhana, traduzida em Portuguez. - Le Sage, Alain René (Typ. de Jose Baptista Morando, 1859)
OCLC: 562048065
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Poor; Fiction; Hard Cover; History

Repertoire de la Doctrine Chretienne ou Cours Complet - Marin, M. L'abbe C. (Aux Bureaux du Journal de La Predication Populaire dt Contemporaine, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage.

Repertoire de la Doctrine Chretienne ou Cours Complet - Marin, M. L'abbe C. (Aux Bureaux du Journal de La Predication Populaire dt Contemporaine, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage.

Repertoire de la Doctrine Chretienne ou Cours Complet - Marin, M. L'abbe C. (Aux Bureaux du Journal de La Predication Populaire dt Contemporaine, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage.

Rafaella - Pellico, Silvio (Librairie de P. Lethielleux ; H. Casterman, 1859)
OCLC: 422248269
Keywords: 10.Cover Damage; 2.Damage; Condition: Poor; Hard Cover

History of the reign of Philip the Second, King of Spain - Prescott, William Hickling (Routledge, Warne & Routledge, 1859)
OCLC: 1080170971
Keywords: 1556-1598; 18.Bookworm; 22.stamp; 28.Iron-gall ink; Condition: Fair; Espagne Histoire 1556-1598 (Philippe II); Hard Cover; History; Philip II; King of Spain; 1527-1598; Spain; Spain History Philip II; 1556-1598

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Histore Universelle de L'eglise Catholique - Rohrbacher, L'abbe (Gaume Freres, et J. Duprey, 1859)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; Good

Flos Sanctorum ou Santuario Doutrinal - Sarmento, Pe. Francisco J. M. (Tupi. Acadreal Scienc, 1859)
Keywords: 1.Conservation 保護; 2.Damage

Flos Sanctorum ou Santuario Doutrinal - Sarmento, Pe. Francisco J. M. (Tupi. Acadreal Scienc, 1859)
Keywords: 1.Conservation 保護; 2.Damage

Flos Sanctorum ou Santuario Doutrinal - Sarmento, Pe. Francisco J. M. (Tupi. Acadreal Scienc, 1859)
Keywords: 1.Conservation 保護; 2.Damage

Theologiae Pastorialis, Systema - Schenkl, Manuri de (Sumtibus Et Geogii Joseph Manz, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 18.Bookworm; 2.Damage

Theologiae Pastorialis, Systema - Schenkl, Manuri de (Sumtibus Et Geogii Joseph Manz, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 18.Bookworm; 2.Damage

Theologiae Pastorialis, Systema - Schenkl, Manuri de (Sumtibus Et Geogii Joseph Manz, 1859)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 18.Bookworm; 2.Damage